Performin Nietzsche: autoethnography as a metodological path applied to the creative process of Adeuzará (Revista NUPEART, 2023)
This article discusses the interdisciplinary creative process of the art collective ADEUZARÁ (Belo Horizonte, Minas Gerais) based on a research on the life and work of the German philosopher Friedrich Nietzsche. The work was originally presented as a doctoral thesis in the Graduate Program in Language Studies (POSLING) of CEFET-MG. ADEUZARÁ chose "Thus Spoke Zarathustra: a Book for Everyone and for Nobody" as the main motto of the collective's study and artistic creation. Developed between 2013 and 2017, ADEUZARÁ articulated several languages in its poetics, unfolding in the production and creation of street performing art, radio broadcasts and a scenic-sound installation. The study was developed based on documentary research, using the methodology of autoethnography. The author starts from the experience as a co-creator in the collective and then writes about his experience during the process. To this end, an appreciation of the creative expression of this poetics was carried out: logbooks, audiovisual records, interviews with co-creators and partners involved in the process. The article makes an excerpt of ADEUZARA's creative movement and addresses the conception of the scenic-sound installation GRIETZSCHE, pointing out the autoethnographic method as a possible path for art research, especially in relation to artistic research in the academic sphere. Among the conclusions of the study, this work highlights how street performance art provides other ways of seeing, being, being, occupying and living in and with the city. As for the scenic and sound installation, the role of intermediality as a process is emphasized, and the event does not have the character of a work/product, but of a transitory and fleeting event.
Keywords: Nietzsche; creation process; languages; performative action; autoethnography